Aprotinin in pediatric neuromuscular scoliosis surgery - Kasimian, Stepan (Springer-Verlag, 2008)
Reduction of blood transfusions in patients with neuromuscular scoliosis can decrease potential complications such as immune suppression, infection, hemolytic reaction and viral transmission. Aprotinin (Trasylol(®), Bayer), an antifibrinolytic, has proven to be effective in reducing blood loss in cardiac and liver surgery, but little data exists in patients undergoing spinal fusion for neuromuscular scoliosis. The purpose of this study was to evaluate the safety and efficacy of aprotinin in pediatric neuromuscular scoliosis patients undergoing spinal fusion. The medical records of all patients undergoing initial spinal fusions for neuromuscular scoliosis between January 1999 and March 2003 were reviewed to determine demographic data, perioperative data, wound drainage and number of transfusion required. Cases were compared to a matched group of historical controls. We had 14 patients in the aprotinin group and 17 in the control group. Total blood loss in the aprotinin group was significantly lower compared to the control group (715 vs. 2,110 ml; P = 0.007). Significantly less blood loss occurred in the aprotinin group when blood loss per kilogram was evaluated as well (23 vs. 60 ml/kg, respectively; P = 0.002). Intra-operative packed red blood cell (PRBC) transfusions were also significantly lower in the aprotinin group (1.25 vs. 3.16 units; P = 0.001). No clinical evidence of anaphylaxis, deep vein thrombosis (DVT) or renal failure was observed in the aprotinin group. After considering the price of drug therapy, operating room time, and the cost of blood products, the use of aprotinin saved an average of $8,577 per patient. In our series, the use of aprotinin resulted in decreased blood loss and a decreased rate of transfusions in children with neuromuscular scoliosis undergoing extensive spinal fusion. At out institution, the use of aprotinin is safe and cost effective for patients with neuromuscular scoliosis.